2020
DOI: 10.3390/info11090423
|View full text |Cite
|
Sign up to set email alerts
|

From Traditional to VR-Based Online Education Platforms: A Model of the Mechanism Influencing User Migration

Abstract: VR technology can help create optimal virtual learning spaces. Such spaces offer new visual experiences that break through the limitations of time and space and greatly stimulate people’s imagination and creativity in learning. Currently, the bandwidth required for such spaces limits the large-scale application of virtual reality (VR) technology for this purpose. With the large-scale deployment and application of high-speed networks, however, online education platforms based on VR technology will be better abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…VR is widely used in education, and it refers to the presentation of virtual or real interactive three-dimensional environments (Fowler, 2015). Chen et al (2020) argue that VR provides a new visual experience that breaks the limits of time and space. It greatly stimulates people’s imagination and creativity in learning (Chen et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…VR is widely used in education, and it refers to the presentation of virtual or real interactive three-dimensional environments (Fowler, 2015). Chen et al (2020) argue that VR provides a new visual experience that breaks the limits of time and space. It greatly stimulates people’s imagination and creativity in learning (Chen et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chen et al (2020) argue that VR provides a new visual experience that breaks the limits of time and space. It greatly stimulates people’s imagination and creativity in learning (Chen et al , 2020). Xie et al (2019) conducted a study on the use of VR tools to improve students’ learning of Chinese language, and the data showed that the content and vocabulary of participants’ oral reports were statistically significantly higher when using VR tools than when not using VR tools, so it can be seen that VR tools help prepare and encourage active learning (Xie et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature reviewed also indicates that service quality expectations are likely based on excellence. In contrast, ratings of satisfaction are more likely to be based on a wide range of quality defects (Chen, Liu, Chang, Gui, & Na, 2020;De Oña, 2021;Jin, Lee, Slocum, & Merkebu, 2018;Naumovska-Saveska, Tomovska-Misoska, Efremov, & Petrovska, 2021). More specifically, there could be potential customer satisfaction, including service quality.…”
Section: International Journal Of Asian Social Sciencementioning
confidence: 99%
“…Customer satisfaction surveys are often closely related to measuring service quality (Chen et al, 2020;De Oña, 2021;Pakurár et al, 2019;Rita, Oliveira, & Farisa, 2019). Satisfaction is the customer's feelings and attitude towards the service after using the service.…”
Section: Service Qualitymentioning
confidence: 99%
“…Lee [50] presented the several core factors necessary for VR-based content design: collecting information on accident situations to be implemented using VR technology, setting curriculum and educational goals in consideration of educational level and difficulty, etc., and creating realistic educational scenarios with which learners can engage. Chen et al [51] applied reality to form the learner's risk perception among the components of the existing safety education and training contents, such that the learner was immersed in the contents of education and the contents were embodied. An evaluation of educational effectiveness was also presented.…”
Section: Virtual-reality-based Safety Education and Trainingmentioning
confidence: 99%